Retraksi gingiva sebelum pencetakan untuk mendapatkan gigitiruan cekat yang ideal Gingiva retraction before impression to get an ideal fixed prostheses restoration - Hanoem Eka Hidajati; Ratri Maya Sitalaksmi (DiscoverSys Inc., 2011)
Since the discovery of making impression for fixed protheses directly in the mouth, impresions material or negativeform resembling the tooth and surrounding structures are used to get a working model. Impression received must bea real replica of a tooth that has been prepared. The impressions that are not clear between the borders withgingival preparation are the common cause of failure when impression was made. Good impression is one of thesupporting factors to produce a fixed protheses which can well adapted to the tooth tissue that does not cause leaksand dissolve the cement. So the tooth is protected from caries and the fixed denture can have a better function,durable and good aesthetic. These problems can be overcome by performing gingival retraction on abutment teeththat have been prepared. Gingival retraction can be done mechanically, chemically on prepared abutment teeth byusing gingival cord or paste, and by using electrosurgery.